Nashville noir [large type] : a Murder, she wrote mystery - Bain, Donald, 1935-2017 (Fletcher, Jessica. Murder, she wrote., 2015)
Weeks after young Cabot Cove singer Cyndi Gabriel is sent on scholarship to Nashville, everyone is stunned when she's charged with the murder of a brash music publisher. Now it's up to Jessica to uncover the truth -- or poor Cyndi will never get the chance for an encore.